14. Calypso® with DynamicEdge™ gating for large antero-posterior torso dimensions patients: Case report. (December 2017) - Dubouloz, A.; Rouzaud, M.; Koutsouvelis, N.; Nouet, P.; Zilli, T.; Dipasquale, G.
Abstract : Introduction: Calypso® (Varian Medical System) with DynamicEdgeTM gating for prostate cancer is dependent of patient thickness, transponder implantation and isocenter position. We report a method to extent the amount of large anterior-posterior torso patients that can be tracked during radiotherapy, when post-implantation geometry could only be used for localization. Methods: Since January 2016, 38 patients treated for prostate cancer benefited from Calypso® in our department. Calypso® requires 3 electromagnetic transponders to be implanted into the left base, right base and apex of the prostate. All patients were treated on a TrueBeam machine, with volumetric modulated arc therapy (VMAT). The isocenter was initially set as the centroid of the transponders. The distance from the anterior skin surface to the transponder closest to the table (SST) and the distance from the anterior skin surface to isocenter (SSI) were measured on the simulation CT images. For SST > 25 cm or SSI > 23 cm, the patient is not a candidate for Calypso®. For 25 cm > SST > 19 cm or 23 cm > SSI > 17 cm, Calypso® can only localize the transponder but cannot track them during treatment. For SST > 19 cm (enforced limit 21 cm) or SSI > 17 cm, Calypso® is fully used as localization and tracking tool (L&T). Three out of 38 patients had 23 cm > SSI > 17 cm and one of these 3 patients had SST = 20.5 cm (within enforced limit). For these 3 patients, an initial dosimetric plan (P Init) was optimized with the isocenter in the centroid position. A 2nd dosimetric plan (P Shift) was optimized with the isocenter shifted anteriorly in order to obtain SSI > 17 cm. Dose prescriptions were: 64 Gy to the prostatic bed and 70.4 Gy to an involved node in 32 fractions for patient #1, 36.25 Gy in 5 fractions to the prostate for patient #2, and 50.4 Gy in 24 fractions to the prostate and pelvis followed by a boost of 24 Gy in 6 fractions to the prostate for patient #3 (4 plans in total). We report a dosimetric comparison between P Init and P Shift on PTV, rectal wall (RW), bladder wall (BW) and penile bulb (PB). Quality assurance was performed for all plans (absolute dose and PortalVisionTM measurements). Results: After isocenter shift, SSI were set to 16.9, 15.7 and 15.6 cm for P Shift compared to 20.2, 18 and 18.6 cm for P Init, respectively. The PTVs maximum, minimum and mean doses differences between P Init and P Shift were less than 2%. For RW and BW, mean and maximum doses remained within ±6% of their initial values. PB was the only organ at risk negatively impacted for all 3 patients by the isocenter shift (max 25%). Field sizes for P Shift were bigger so combination of scattered dose and larger penumbra increased the dose to PB located at the border of PTVs. Gamma Index (3%/3 mm) passing rate for PortalVisionTM measurements were superior to 96.1% and absolute measurements were within 5% of the expected value. The 3 patients were treated with P Shift. Conclusions: In patients with initial SSI > 17 cm, an anterior shift of the isocenter allows an accurate Calypso® localization and tracking without compromising target coverage and OARs sparing.